A unified framework for the estimation of intra and inter country food purchasing power parities: India, Indonesia and Vietnam. Issue 1 (11th April 2016) - Majumder, Amita; Ray, Ranjan; Sinha, Kompal
Abstract : Purpose: The purpose of this paper is to extend the methodology proposed in Majumder et al. (2012) for the estimation of the item-specific purchasing power parities (PPPs) within countries, to the cross-country context. It estimates item-specific intra-country PPPs (i.e. spatial prices) and inter-country PPPs in a unified framework using unit records of household food expenditures from three Asian countries: India, Indonesia and Vietnam, covering contemporaneous time periods. The study addresses a key limitation of the International Comparison Program (ICP) exercise, namely, that it treats all countries, large and small, as homogeneous entities. Moreover, it directly calculates bilateral PPPs between countries based on their expenditure patterns and prices alone and directly estimates the price-level indices (PLI) and their standard errors, allowing formal tests of the hypothesis of PLI being unity. The usefulness of the estimated PPPs is illustrated by applying them to comparisons of real food expenditures between the three countries, and benchmarking the comparisons with those using the ICP PPPs. Design/methodology/approach: The methodology is based on the fact that a spatial price index can be viewed as a true cost of living index (TCLI). Using a general cost function underlying the Rank 3 quadratic logarithmic systems, the TCLI is calculated for a reference utility level. Findings: The study provides formal statistical tests of the hypothesis of item invariance of the PPPs. The usefulness of the proposed methodology is illustrated by applying the estimated PPPs in comparisons of food expenditures between subgroups in the three countries. The sensitivity of the expenditure comparisons to the use of item-wise PPPs underlines the need to provide price information on highly disaggregated PPPs to a much greater extent than the ICP has done to date. Research limitations/implications: The choice of these three Asian countries was dictated by the fact that, though comparability of items between them remains an issue as with all cross-country comparisons. Also, in the absence of price data, this study followed the practice inMajumder et al. (2012, 2015a, 2015b ) in using as proxies the raw unit values of the food items, but adjusted for quality and demographic factors using the procedure introduced byCox and Wohlgenant (1986) and extended byHoang (2009) . Practical implications: It addresses some limitations of the ICP, namely, ICP treats all countries as single entities with the purchasing power of the country's currency assumed to be the same in all regions within the country, ICP uses the US dollar as the numeraire (this ignores the fact that the PPPs required in bilateral welfare comparisons between developing countries with vastly different consumption habits from the "international norm" are quite different from the ICP PPPs) and ICP uses distribution invariant prices to calculate PPPs, which overlooks the fact that the poor pay different prices from the "representative" individual. Social implications: This study highlights the importance of estimating and using item-specific PPPs in cross-country comparisons by formally testing and rejecting the assumption of item invariant PPPs and by providing empirical evidence that they do make a difference to the welfare comparisons between countries. This study provides PPPs based on food items only, which may be more relevant for poverty comparisons. Originality/value: It introduces, for the first time, the concept of item-specific PPPs between countries as estimable parameters and operationalizes this concept by using them in cross-country welfare comparisons.